BEKTASHI’S IN KIRKUK - OMAR NAJI, Sunbl (Atlas Journal, 2022)
In this article, Bektashi’s in Kirkuk was interviewed with the source people of the sect, and general information about Bektashis’s was given. In addition, information is given about the beliefs of Kirkuk Bektashi’s. At the same time, stories were written about the people of the Bektashi order mentioned in the past. Finally, the poems written by Kirkuk Bektashi’s are shown. The poems written by Kirkuk Bektashi’s and all the information obtained from the manuscript documents were transcribed from the old script to the new letters.